KANTIAN CHOICES AND BIMYTHICALNESS: ABOUT THE STARTING POINT FOR THE IMAGOLOGIST - Wiśniewska, Lidia (Porównania, 2019)
The article consists of four parts. The first one, Imagology and Kant, reminds of Manfred Baller’s concepts that connect imagology with Kant’s conception. However, it also brings to mind Joep Leerssen’s ideas which ascribe anti-essentialism and not essentialism of the images themselves to the imagologist. The second part, Images and Hermeneutics, that is Ricoeurian Addition/Extension Aiming at Fullness, presents the cognitive approach that connects the two opposing philosophical concepts (by Nietzsche-Freud and by Kant) basing on the two myths – that of God and that of Nature (representing arché and télos). The third part, Images and Constructures. Kantian Subtracting/Diminishing, that is Aiming at the Form, shows how Kant rejects pathologic, in his opinion, aspects of reality (dialectics, coincidence, empiricism, etc.) that fit in the myth of Nature, or the aspects of man (dream, emotions, spontaneity) to justify and to acknowledge as universally applicable those based on the myth of God (also demanding its existence). The fourth part is a collection of questions and answers of why the two mentioned myths and their interrelations may be considered a basis of culture and the comparison of its fields. However, the question of the relationship between the myths as regards imagology remains open.